Heidegger's philosophy of art (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Heidegger's philosophy of art is considered a philosophy that is different from what we are used to with other philosophers. He made art as one of ways to expose the truth, because the quiddity of existence manifests from appearance of the existed and it's openness by the work of art, within a stressful relationship between the world and the earth. The art has to bring them closer, so that man can create a world that contains all possibilities, so he used the instrument to bring for the earth from its obsession and make the world appear. What we want to get to in this research is knowing the basic ideas about Heidegger's philosophy of art, and explaining the concept of aesthetics from his point of view. This was done through our presentation of his philosophy and the subjects that he adopting. "The origin of work of art, the relationship between world and earth, and the concept of truth", and treated by examination using a method that combines phenomenology with ontology to answer the question: "What the quiddity of art is?"